Endo-lysosomal Aβ concentration and pH trigger formation of Aβ oligomers that potently induce Tau missorting - Marie P. Schützmann (Nature Portfolio, 2021)
Aβ oligomers (AβO) are thought to represent the main toxic species in Alzheimer’s disease but very high Aβ concentrations are required to study them in vitro and it remains unknown what role these off-pathway oligomers play in vivo. Here, the authors use a dimeric variant of Aβ termed dimAβ, where two Aβ40 units are linked, which facilitates to study AβO formation kinetics and they observe that Aβ off-pathway oligomer formation is strongly accelerated at endo-lysosomal pH, while amyloid fibril formation is delayed. Furthermore, the authors demonstrate that dimAβ is a disease-relevant model construct for pathogenic AβO formation by showing that dimAβ AβOs target dendritic spines and induce AD-like somatodendritic Tau missorting.